KIMIA DARAH KUDA SILANG YANG DIPELIHARA DI DAERAH ISTIMEWA YOGYAKARTA DAN JAWA TENGAH - ALFIANI, ADE FITRIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Blood chemical can used to describe organs functional status in normal physiology condition or in abnormal condition caused by infectious or non infectious on organs such as : kidney, liver, heart, and muscle. The purpose of this study was infestigation the normal average of Serum Glutamic Piruvic Transaminase (SGPT), Serum Glutamic Oxaloacetic Transaminase (SGOT), Blood Urea Nitrogen (BUN), and creatinine of local horses breed in DIY and Central Java. This study used 7 of SNI local horses breed in District of Yogyakarta and Central Java, where 4 of them from Special District of Yogyakarta stable and the other from Central Java stable. There were 5 female horses and 2 male horses aged around 3 - 6 years old. 5cc of blood sampling which was taken through jugularis vein kept in a tube no antikoagulan to get a serum then tested at Jogja Animal Clinic. The content of SGPT, SGOT, BUN, and creatinine measured by automatic blood analyzer model RT-1940C (Synchron clinical system CX5CE, Beckam USA). The result of this study showed that range of SGPT, SGOT, BUN and creatinine was 3,93 ; 14,35 IU/L, 173,7 â 314,8 IU/L 15,69 â 23,97 mg/dL, and 1,75 â 2,13 mg/dL respectively.